2021
DOI: 10.1155/2021/7202319
|View full text |Cite|
|
Sign up to set email alerts
|

Effect of Applying Binocular Visual Training after Slanted Lateral Rectus Recession on Orthophoric Rate and Binocular Visual Function Recovery on Patients with Convergence Insufficiency-Type Intermittent Exotropia

Abstract: Objective. To explore the effect of applying binocular visual training after slanted lateral rectus recession on orthophoric rate and binocular visual function recovery on patients with convergence insufficiency-type intermittent exotropia (CI-IXT). Methods. A total of 76 CI-IXT child patients treated at the Strabismus and Pediatric Ophthalmology Department of our hospital from June 2019 to June 2020 were selected as the research objects, and those who met the inclusion criteria were equally divided into group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Dai et al . [ 18 ] promoted the recovery of binocular visual function by conducting binocular visual training for children with intermittent exotropia after the operation, with results showing high safety.…”
Section: Discussionmentioning
confidence: 99%
“…Dai et al . [ 18 ] promoted the recovery of binocular visual function by conducting binocular visual training for children with intermittent exotropia after the operation, with results showing high safety.…”
Section: Discussionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%